ISLAMIC CONSUMPTION ETHICS ON SKINCARE - Noor Iffatin Nadhifah (JINGJI : Jurnal Ekonomi, Bisnis dan Manajemen, 2024)
specifically for consumers to be careful about the ingredients of skincare and its suitability to the type of consumer's skin. This study aims to provide consumer insight into consuming skincare according to the ethics of consumption in Islam. The research method used is the descriptive method used to collect actual data, this method generally uses a qualitative approach, so that a researcher when going into the field does not bring a data collection tool, but directly conducts observations or observations of evidence while collecting data and conducting analysis. The results of this study are that consumers must be grateful for God's gift (beauty) by maintaining it, this is done by consuming skincare that can be obtained from anywhere in a halal and good way. Here consumers have the free will to determine which skincare products are needed that are in accordance with the consumer's budget, but do not forget that consumers must also be responsible for all of that to Allah, themselves and others.